Britain's Korean war : Cold War diplomacy, strategy and security, 1950-53 - Hennessey, Thomas (Manchester University Press, 2013)
This book investigates the UK's experience as a junior partner in the only Cold war conflict where some of the main protagonists confronted each other on the battlefield. The author assesses the strains within the 'Special Relationship' between London and Washington and offers a new perspective on the limits and successes of British influence.